Eddy current nondestructive mapping of C/C-SiC composites - Srivastava V.K.; Udoh A.; Maier H.-P.; Knoch P.; Maile K. (My University, 2025)
Eddy current technique using a C-scan probe coil system has been tested quantitatively in the laboratory for the evaluation of various type of surface irregularities, i.e. surface notch/crack, sub-surface notch/crack, carbon coated surface and oxidized surface of C/C-SiC composite materials. The results show, that the eddy current technique can also be used as a sensitive tool for monitoring defects in C/C-SiC composite materials.